BINAURAL BEATS AS AN INTERVENTION TO REDUCE ACADEMIC ANXIETY IN FIRST SEMESTER STUDENTS - Nurhalimah Nurhalimah; Omi Haryati; Indriana Rakhmawati; Wartonah Wartonah; M Zaky Akbar; Nadhia Elsa Silviani (Poltekkes Kemenkes Jakarta III, 2025)
Anxiety and difficulty concentrating are often experienced by first-year college students, especially those with introverted personalities, poor coping mechanisms, low adaptability, and an inability to manage stress. These conditions can impact their academic performance. This is a quantitative study with a pre-experimental design using a one-group pretest-posttest design. A sample of 57 students in the Applied Undergraduate Study Program, Department of Nursing, Poltekkes Jakarta III, was selected through purposive sampling. Data were analysed using the Wilcoxon signed-rank test. The results showed that the average academic anxiety score before the intervention was 55.95, while after the intervention it decreased to 41.00, with a p-value of 0.001. These findings indicate that binaural beats are effective in reducing academic anxiety levels in nursing students at Poltekkes Kemenkes Jakarta III, thus offering an alternative approach to addressing students' academic anxiety.